Is it Possible to do Legal Revolution in Indonesia - Kurniawan Tri Wibowo (Budapest International Research and Critics University, 2022)
Is it possible to conduct a revolution in criminal procedure law in Indonesia, the answer is possible, but whether or not to come back again becomes a debate in the discussion of the Criminal Procedure Code Bill. Displacement of legal traditions is not prohibited. Humans and the complexity of their legal culture continue to grow, so the law is there for humans, not the developing human being forced in such a way as to enter into certain legal schemes, which of course are incompatible and will always be left behind from civilization. When there is a problem in criminal procedure, the law must be reviewed and corrected, not humans who are forced to be included in the criminal procedure law scheme in certain legal traditions. Japan, France and Italy are examples of countries that have revolutionized the procedural law for speeches to get the right formula and be close to the truth. The revolution is carried out in a flowing way, not limited to a certain form and not stop at a certain point. For example, Japan does not directly apply the adversarial system, but it first applies continental European laws that are inquisitive and akusatoir. Likewise Italy where the Constitutional Court that was formed at that time actually ruffled the concept of the speech justice system, but Italy still found a format of criminal justice that was suitable for the country.